2016
DOI: 10.1161/jaha.115.003129
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Rehospitalizations for Unstable Angina and Unplanned Revascularization Following Acute Myocardial Infarction

Abstract: BackgroundRehospitalizations following acute myocardial infarction for unplanned coronary revascularization and unstable angina (UA) are often included as parts of composite end points in clinical trials. Although clearly costly, the clinical relevance of these individual components has not been described.Methods and ResultsPatients enrolled in a prospective, 24‐center, US acute myocardial infarction registry were followed for 1 year after an acute myocardial infarction for rehospitalizations, that were indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…We demonstrated that a higher TyG index was independently associated with worse cardiovascular outcomes, mainly driven by the increase in unplanned revascularization. Patients with unplanned revascularization have been demonstrated to have substantially higher risks of subsequent rehospitalization than subjects without such events [ 27 ]. The progression of lesions was the main factor contributing to unplanned revascularization in the present cohort, rather than in-stent restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that a higher TyG index was independently associated with worse cardiovascular outcomes, mainly driven by the increase in unplanned revascularization. Patients with unplanned revascularization have been demonstrated to have substantially higher risks of subsequent rehospitalization than subjects without such events [ 27 ]. The progression of lesions was the main factor contributing to unplanned revascularization in the present cohort, rather than in-stent restenosis.…”
Section: Discussionmentioning
confidence: 99%